Structure, Tasks and Training of the Slovak Border Police - Olha Khamaziuk (Pedagogical Discourse, 2020)
The article describes the organizational structure of the Presidium of the Police Force of the Ministry of Interior of the Slovak Republic, indicates its competence and the basic divisions. The main tasks, that are set before the border department of the Slovak Republic have been described. Peculiarities of the border police professional training in departmental educational institutions are characterized. The urgency of the study is due to the fact that Ukraine’s integration into the European Union requires high-quality reform of Ukrainian border agency, which is impossible without borrowing experience from European countries, which law enforcement agencies have fully integrated their activities to consolidate issues at the international level and adapted the professional training system to a common European professional education system.The study showed that the Bureau of Border and Foreign Police (BFPB) of the Presidium of the Police Force in Slovakia is the equivalent of Ukrainian border guard agency and is responsible for guarding the state border of the Slovak Republic and controlling the border crossing. As part of the European Union’s integrated border management and protection of the Schengen external borders, Slovakia has reformed its border agency in line with European requirements, including the Schengen Borders Code, FRONTEX, risk analysis (to exchange information within the EU), the national unit for combating illegal migration and other divisions. The above-mentioned Bureau has a three-level governance structure, which is formed within the framework of European norms. Thus, the central level is the Office in Bratislava, the regional level is the 4 Directorates of the BFPB, which are located in Bratislava, Sobrance, Prešov and Banská Bystrica cities, the local level is the border control divisions, checkpoints and airports.The Sobrance BFPB Directorate is responsible for controlling the Slovak-Ukrainian frontage of the state border. Its organizational structure includes a number of units that deal directly with border control and border traffic across the state border, namely: 10 border control divisions, 5 checkpoints and 3 airports. Border control is based on a four-level control system by the Slovak Party on the border with Ukraine. Important units of the Directorate are also the National Unit for Fight against Irregular Migration and the Aliens Police Unit, which are closely linked to the border police.